Underwater cultural heritage and extreme events: Storm impacts under climate change - Luigi Germinario; Stuart J. McLelland; Claudio Mazzoli (Proceedings of the National Academy of Sciences, 2026)
Extreme weather events cause severe ecological disruptions to the marine environment and socioeconomic impacts, while also endangering the evidences of human history resting underwater. Storms, in particular, generate high-intensity currents that lead to substantial material loss and textural alteration. We present a quantitative risk assessment of underwater cultural heritage exposed to storm events, considering climate change and the vulnerability of historical stone materials. We monitored the amount, rate, and patterns of stone erosion through innovative flume simulations and surface three-dimensional modeling, investigating its changes with time, current velocity, and properties of the materials and suspended sediments. The experimental results were combined with global models of storms and ocean currents under present and future climate, accounting for projected changes in storm intensity and frequency, climate scenarios, geographic settings, and seabed environments. Our findings show that even a single storm may result in irreversible damage to historical surfaces, erasing key morphological and textural features and compromising their legibility—especially in global hotspots such as tropical regions. In a future dominated by high greenhouse gas emissions and increasing extreme events, the vulnerability of archaeological stone could locally rise to more than double present levels. Extreme events and climate change pose major threats to the preservation of underwater cultural heritage and its historical, touristic, educational, and scientific values, requiring the development of long-term adaptation and protection strategies.